Optimization In Develop The LTE Site Planning Jabodetabek Region Using Linear Programming Method In Pycharm And POM-QM Software, Case Study PT. XYZ - Amelia Fahmawati Subiyanto; Rio Aurachman; Maria Dellarosawati (Universitas Trunojoyo Madura, 2018)
PT. XYZ is an open company developed in mobile telecommunication in Indonesia. The company was established to meet the needs of customers throughout all of the region in Indonesia. To determine how many sites should be built with limitations of budget would be the constraints, then it takes the objective function derived from calculations using linear programming methods. In this case, the calculation and analysis which aims to develop the plan of 4G LTE technology which has four types, those are LTE900, LTE1800, LTE2100, and LTE2300 in JABODETABEK region for this study by using pycharm software with PULP package and compared using POM-QM software. The results obtained by using both software shows the same number as follow, LTE types that must be built sequentially from the most to the least are LTE2100 12,580 sites, LTE2300 2.044 sites, LTE1800 390 sites, and LTE900 0 sites. Based on these results, if the company implemented these results in building the site for each type of LTE, then the maximum total revenue that can be obtained by the company is Rp 2.452.380.953.518,722.